Criteria for Selection of Educational Materials in the Training of Listening at the Senior Stage of the Secondary High School - КосовичOlga (Pedagogical Discourse, 2021)
This paper deals with the teaching methodology of listening comprehension, which should focus on the ability to understand a foreign language by listening once or twice with or without visual non-verbal support and then using it in various speech activities and speech situations. By mastering listening techniques, students will learn to analyse communication situations (place, time, interlocutor, purpose of contact) and decide on a programme of their linguistic and non-linguistic behaviour that is oriented towards a communicative goal, taking into account the communication situation. The organisation of learning material, techniques and methods of teaching listening comprehension, the system of exercises should take into account the student’s personality – his or her needs, motives, abilities, activity and intellect. It is also worth mentioning the use of modern technologies in teaching with the use of Internet resources, which are becoming increasingly important today. The Internet is regarded as one of the leading cutting-edge learning technologies, as its possibilities in the field of education are limitless: organisation and planning of the learning process, search for information for both the teacher and his/her students, selection of texts for students with different levels of English proficiency.